Rho-Kinase Inhibition Ameliorates Dasatinib-Induced Endothelial Dysfunction and Pulmonary Hypertension - Fazakas, Csilla; Nagaraj, Chandran; Zabini, Diana; Végh, Attila G.; Marsh, Leigh M.; Wilhelm, Imola; Krizbai, István A.; Olschewski, Horst; Olschewski, Andrea; Bálint, Zoltán (Frontiers in Physiology, 2018)
The multi-kinase inhibitor dasatinib is used for treatment of imatinib-resistant chronic myeloid leukemia, but is prone to induce microvascular dysfunction. In lung this can manifest as capillary leakage with pleural effusion, pulmonary edema or even pulmonary arterial hypertension. To understand how dasatinib causes endothelial dysfunction we examined the effects of clinically relevant concentrations of dasatinib on both human pulmonary arterial macro- and microvascular endothelial cells. The effects of dasatinib was compred to imatinib and nilotinib, two other clinically used BCR/Abl kinase inhibitors that do not inhibit Src. Real three-dimensional morphology and high resolution stiffness mapping revealed softening of both macro- and microvascular endothelial cells upon dasatinib treatment, which was not observed in response to imatinib. In a dose-dependent manner, dasatinib decreased transendothelial electrical resistance/ impedance and caused a permeability increase as well as disruption of tight adherens junctions in both cell types. In isolated perfused and ventilated rat lungs, dasatinib increased mean pulmonary arterial pressure, which was accompanied by a gain in lung weight. The Rho-kinase inhibitor Y27632 partly reversed the dasatinib-induced changes in vitro and ex vivo, presumably by acting downstream of Src. Co-administration of the Rho-kinase inhibitor Y27632 completely blunted the increase pulmonary pressure in response to dasatinib. In conclusion, a dasatinib-induced permeability increase in human pulmonary arterial macro- and microvascular endothelial cells might explain many of the adverse effects of dasatinib in patients. Rho-kinase inhibition might be suitable to ameliorate these effects.